A Sorghum Mutant Resource as an Efficient Platform for Gene Discovery in Grasses. Issue 7 (27th June 2016) - Jiao, Yinping; Burke, John; Chopra, Ratan; Burow, Gloria; Chen, Junping; Wang, Bo; Hayes, Chad; Emendack, Yves; Ware, Doreen; Xin, Zhanguo
Abstract : Sequencing of 256 sorghum mutant families uncovered 1.8 million mutations, providing an efficient resource for causal gene/SNP variant to trait association with wide application to cereal crops. Abstract: Sorghum ( Sorghum bicolor ) is a versatile C4 crop and a model for research in family Poaceae. High-quality genome sequence is available for the elite inbred line BTx623, but functional validation of genes remains challenging due to the limited genomic and germplasm resources available for comprehensive analysis of induced mutations. In this study, we generated 6400 pedigreed M4 mutant pools from EMS-mutagenized BTx623 seeds through single-seed descent. Whole-genome sequencing of 256 phenotyped mutant lines revealed >1.8 million canonical EMS-induced mutations, affecting >95% of genes in the sorghum genome. The vast majority (97.5%) of the induced mutations were distinct from natural variations. To demonstrate the utility of the sequenced sorghum mutant resource, we performed reverse genetics to identify eight genes potentially affecting drought tolerance, three of which had allelic mutations and two of which exhibited exact cosegregation with the phenotype of interest. Our results establish that a large-scale resource of sequenced pedigreed mutants provides an efficient platform for functional validation of genes in sorghum, thereby accelerating sorghum breeding. Moreover, findings made in sorghum could be readily translated to other members of the Poaceae via integrated genomics approaches.